The Relationship Between Proprioception, Physical Activity Level, Muscle Endurance, Posture, Sitting Time, Smartphone and Computer Usage in Healthy Young Adults - Depreli, Ozde; Iyıgun, Gozde; Angın, Ender; Oksüz, Sevım; Ozdil, Aytul; Ersoy, Ceren; Bilgin, Betül Fatma (My University, 2024)
Aim: This study aimed to examine the relationship between the proprioceptive sense of shoulder, hip, and knee joints, posture, and muscle endurance in healthy young adults. Methods: 397 volunteers between the ages of 18-25 were included in the study. The proprioception sense of the hip, knee, and shoulder joints was evaluated with a goniometer, and the physical activity level was evaluated with the International Physical Activity Questionnaire- Short Form. The plank, repeated squat, and push-up tests were used to evaluate core muscles, lower body muscles, and upper body muscles endurance respectively. Posture was assessed with Reedco’s Posture Score. Results: A negligible correlation was found between proprioception sense of the shoulder, knee, and hip joints at different angles with the duration of smartphone and computer usage, daily sitting time, posture and core endurance, and lower and upper extremity muscle endurance (p<0.05; r: .103-.207). Conclusions: The results may indicate that posture, core, and limb muscle endurance are not related to the proprioceptive functioning of the joints. Other factors associated with proprioception, such as muscle strength, should be investigated in future studies in individuals with different physical activity levels and symptoms.
Keywords: Posture; endurance; healthy; PProprioception